LANGUAGE SITUATION AND LANGUAGE CONDITION FOR THE EMERGENCE OF BILINGUALISM (American Journal of Interdisciplinary Research and Development, 2022)
If language communication in society is taken into account, it can be visualized as a continuum that is separated into social interaction and communication domains. This is the area where everyday communication takes place in addition to national and ethnic communication. We can talk about the language environment and conditions that lead to bilingualism in this article.